Galileo y Descartes: la matematización de la física - Ortiz Acuña, Leonardo (2015)
We problematize the mathematization to show that, in spite of Descartes’ posterior development of his thought and of his more important contribution to mathematics, his attempt of mathematize physics doesn’t improve Galileo’s mathematization because they apply different methods, methods which suppose a different role for the metaphysics.